Single and Concurrent Effects of Endurance and Resistance Training on Plasma Visfatin, Insulin, Glucose and Insulin Resistance of Non-Athlete Men with Obesity - Seyed Morteza Tayebi; Ayoub Saeidi; Maryam Khosravi (The Society of Aging and Physical Activity (SAPA), 2016)
The purpose of the present study was to investigate the effect of endurance (ET), resistance (RT) and concurrent training (CT) on plasma levels of visfatin, insulin, glucose and insulin resistance of non-athlete men with Obesity. It was a semi-experimental study. Thirty six men [age: 21.48 (0.25), and BF%: 27.39 (0.52)], voluntarily participated in this study after public announcement in university. Main inclusion and exclusion criteria was healthy (no physical illness and inability), obesity [based on WHO's definition body fat percentage (BF%) of over 25] and non-athlete (without regular training during week). They were randomly divided into three groups (n=12) for ET, RT and CT. For 8 weeks (3sessions/week), the candidates participated in ET (25-40 min at 65-85% of maximum heart rate), RT (5exercises, 6sets, intensity: 50-80% of one repetition maximum, volumes: 5, 8 and 12repetitions) and CT (one or a half-term ET and then RT with 3 sets). Blood samples were taken 48 h before the first training session and 48 h after the last training session. The ANCOVA was used for the comparison of the effect of three types of training. The BF% in ET was significantly less than that in RT (p<0.01), and in CT, it was less than that for both ET and RT (p<0.01). Plasma visfatin only, in CT was significantly less than that in RT (p<0.01). Plasma insulin levels in CT were significantly higher than that in ET and RT (p<0.01). Plasma glucose levels in CT were less than that in ET and RT, significantly (p<0.01). Insulin resistance only in CT was less than that in ET significantly (p<0.01). In general, the present study showed that maybe, CT have more effect on the body composition, glucose metabolism and insulin resistance adjustment, which can be effective in preventing obesity and adjusting adipocytokines such as visfatin.